2016
DOI: 10.1111/jpn.12572
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal development of bovine foetuses during gestation is affected by foetal sex and maternal nutrition

Abstract: We aimed to evaluate the effects of maternal nutrition (MN) and foetal sex on the intestinal development of bovine foetuses throughout different days of gestation (DG). Forty-four multiparous, dry Holstein × Gyr cows with average initial body weight of 480 ± 10 kg were fed the same diet of either restricted feeding at 1.15% of body weight (CO, n = 24) or fed ad libitum (overnourished, ON, n = 20). Six cows from CO group and five cows from ON group were slaughtered at 139, 199, 241 and 268 DG, and foetuses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
(63 reference statements)
1
9
0
2
Order By: Relevance
“…Maternal nutrition can also influence the development of the intestinal tract in ruminants, which can affect the digestibility of nutrients and subsequent performance ( 32 , 65 , 66 ). RPM supply to late-gestation ewes increased both the protein expression of intestinal AA transporters and global methylation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal nutrition can also influence the development of the intestinal tract in ruminants, which can affect the digestibility of nutrients and subsequent performance ( 32 , 65 , 66 ). RPM supply to late-gestation ewes increased both the protein expression of intestinal AA transporters and global methylation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hinde et al (2014) found that dams with female offspring produced 5% more milk during lactation than dams with male offspring. Moreover, Gionbelli et al (2017) reported that female bovine fetuses have a greater intestinal mass and villi length compared to their male counterparts, indicating the female fetus appears to have developed to receive these additional nutrients in the colostrum/milk. While an influence of calf sex on growth performance to weaning was not observed, the potential for daughter-biased colostrum and milk production clearly could impart advantages on early growth and survival of calves in a typical cow-calf operation.…”
Section: Discussionmentioning
confidence: 99%
“…Although undernutrition often results in reduced birth weights, the same is not always the case with maternal overnutrition where birth weights tend to be similar between offspring exposed to maternal overnutrition or control diets meeting nutrient requirements [ 22 , 23 , 34 ]. The influence of maternal overnutrition on organ weights and mass is not as predictable as that observed with nutrient restriction, although many similar molecular changes to organ systems have been described [ 23 , 34 , 35 , 36 , 37 ]. The influence of maternal overnutrition specific to the development of male offspring is not well investigated; however, sex-specific responses are becoming more frequently considered.…”
Section: Maternal Under- and Over-nutrition Impacts On Skeletal Muscle And Adipose Tissue Developmentmentioning
confidence: 99%
“…Several genes and biochemical pathways have been implicated in these responses; however, they may differ based on fetal sex and timing and duration of the nutritional insult. A comparison of male and female offspring revealed that male offspring prioritize skeletal muscle development over intestinal development compared to female offspring when exposed to maternal overnutrition in utero [ 34 , 35 ]. Furthermore, male offspring tend to develop skeletal muscle faster than female offspring, which could alter the response to maternal overnutrition and the resulting performance phenotypes [ 34 , 35 ].…”
Section: Maternal Under- and Over-nutrition Impacts On Skeletal Muscle And Adipose Tissue Developmentmentioning
confidence: 99%
See 1 more Smart Citation